2019
DOI: 10.1158/0008-5472.can-18-1790
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic Effects of PPARD Accelerate Colorectal Tumorigenesis, Progression, and Invasion

Abstract: APC mutations activate aberrant b-catenin signaling to drive initiation of colorectal cancer; however, colorectal cancer progression requires additional molecular mechanisms. PPAR-delta (PPARD), a downstream target of b-catenin, is upregulated in colorectal cancer. However, promotion of intestinal tumorigenesis following deletion of PPARD in Apc min mice has raised questions about the effects of PPARD on aberrant b-catenin activation and colorectal cancer. In this study, we used mouse models of PPARD overexpre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 52 publications
0
45
1
Order By: Relevance
“…In addition, GW501516-mediated activation of PPARβ/δ led to the reduced expression of MMP-9 after the BCL6 transcriptionnal repressor dissociation and consequently to the decrease of pancreatic cancer cell invasion capacities [ 13 ]. In contrast to our results, other experimental works reported that the activation of PPARβ/δ by GW501516 significantly increased the migration and invasion of highly metastatic melanoma cells through the upregulation of Snail expression (a transcriptional repressor of cdh1 gene encoding for the E-cadherin) and the decrease of E-cadherin expression [ 44 ], enhanced human cholangiocarcinoma cell proliferation [ 45 ], or enhanced colorectal cancer in APC mutated mice [ 46 ].…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, GW501516-mediated activation of PPARβ/δ led to the reduced expression of MMP-9 after the BCL6 transcriptionnal repressor dissociation and consequently to the decrease of pancreatic cancer cell invasion capacities [ 13 ]. In contrast to our results, other experimental works reported that the activation of PPARβ/δ by GW501516 significantly increased the migration and invasion of highly metastatic melanoma cells through the upregulation of Snail expression (a transcriptional repressor of cdh1 gene encoding for the E-cadherin) and the decrease of E-cadherin expression [ 44 ], enhanced human cholangiocarcinoma cell proliferation [ 45 ], or enhanced colorectal cancer in APC mutated mice [ 46 ].…”
Section: Discussioncontrasting
confidence: 99%
“…The tumor promoting action of GW501516 in Apc mice was confirmed recently and extended by the findings that the PPARβ/δ antagonist GSK3787 suppressed tumorigenesis. PPARβ/δ expression was significantly higher in human colorectal cancers compared to adenomatous polyps and normal mucosa [50] and also in the malignant cells-invasive front versus their paired tumor centers and adenomas-and proinvasive pathways (connexin 43, PDGFRb, AKT1, EIF4G1 and CDK1) were upregulated in response to PPARβ/δ stimulation [17]. Again, the opposite result has also been published for human and mouse tumor samples [51], while another important report using human colorectal cancer samples confirmed high expression of PPARβ/δ and COX2, which was correlated with the incidence of liver metastasis and identified as significant independent prognostic factor [52].…”
Section: Intervention Outcome Referencementioning
confidence: 95%
“…Previous studies have shown that CDK1 is involved in the progression of multiple types of cancer, including colorectal cancer, liver cancer, and lung cancer. Furthermore, the upregulation of CDK1 is associated with reduced survival time for these diseases [34][35][36]. Xue et al [37] reported that the activity of CDK1 is highly elevated in CRC tissues compared to noncancerous tissues, and it predicts distant metastasis risk in CRC; CDK1 can promote the progression of CRC through phosphorylation of JAK1 to activate the JAK/ STAT3 signaling pathway.…”
Section: Mki67mentioning
confidence: 99%